SEJARAH DAN REFLEKSI KRISTIANI ATAS PERKEMBANGAN SISTEM BILANGAN DALAM BERBAGAI PERADABAN KUNO [HISTORY AND CHRISTIAN REFLECTION ON THE DEVELOPMENT OF NUMERAL SYSTEMS IN VARIOUS ANCIENT CIVILIZATIONS] - Tarapraing, Angelika; Tampubolon, Ferdinand; Sinaga, Stefani; Listiani, Tanti (Universitas Pelita Harapan, 2025)
This article explores the development of numeral systems across various ancient civilizations and connects these developments to Christian reflections on knowledge as a divine gift. Employing a qualitative approach through library research, the study traces the evolution of numeral systems in Egypt, Babylon, China, Greece, Rome, and the Hindu–Arabic tradition, along with the contributions of influential figures such as Ahmes, Liu Hui, Pythagoras, Brahmagupta, and Al-Khwarizmi. Through descriptive and chronological analysis, the study illustrates how practical needs, cultural contexts, and spiritual values shaped the formation of diverse numerical representations. The article emphasizes that numbers are not merely computational tools but cultural artifacts and intellectual symbols refined across generations. Additionally, Christian theological reflection offers a value-centered framework that affirms knowledge—including mathematics—as an expression of gratitude and a means of serving others. This study seeks to enrich mathematics education by presenting a more meaningful integration of historical and theological perspectives. BAHASA INDONESIA ABSTRACT: Artikel ini mengkaji evolusi sistem bilangan dalam berbagai peradaban kuno dan mengaitkannya dengan refleksi iman Kristiani mengenai makna pengetahuan sebagai anugerah ilahi. Menggunakan pendekatan kualitatif melalui studi pustaka, penelitian ini menelusuri perkembangan sistem bilangan di Mesir, Babilonia, Cina, Yunani, Romawi, hingga dunia Hindu-Arab, serta peran tokoh-tokoh penting seperti Ahmes, Liu Hui, Pythagoras, Brahmagupta, dan Al-Khwarizmi. Analisis dilakukan secara deskriptif dan kronologis untuk mengungkap bagaimana kebutuhan praktis, konteks budaya, dan nilai spiritual mendorong munculnya beragam sistem representasi bilangan. Artikel ini menegaskan bahwa bilangan bukan sekadar alat hitung, tetapi merupakan produk budaya dan simbol intelektual manusia yang berkembang dari generasi ke generasi. Di samping itu, refleksi iman Kristen menjadi bingkai nilai yang memperkuat pandangan bahwa pengetahuan termasuk matematika merupakan sarana untuk bersyukur dan melayani sesama. Kajian ini diharapkan dapat memperkaya wawasan pembelajaran matematika dengan pendekatan historis dan teologis yang lebih bermakna.